Effect of the tactic structure on the chiroptical properties of helical vinylbiphenyl polymers. Issue 28 (21st June 2019) - Li, Xiaofu; Wang, Rong; Wu, Chunji; Chen, Junxian; Zhang, Jie; Cui, Dongmei; Wan, Xinhua
Abstract : The effect of a tactic structure on the chiroptical properties of helical vinylbiphenyl polymers is systematically studied. Abstract : To shed light on the stereomicrostructure effect on the conformation of helical vinyl polymers, a pair of enantiomeric monomers, (+)-2-[( S )- sec -butoxy]-5-(4′-hexyloxyphenyl)styrene and (−)-2-[( R )- sec -butoxy]-5-(4′-hexyloxyphenyl)styrene, were synthesized and polymerized through radical, anionic and coordination polymerization under various conditions. The presence of strong steric hindrance between the large neighboring biphenyl pendants drove the main chains of the resultant polymers to adopt stable helical conformations in solution. Isotactic-rich polymers displayed optical rotations opposite to those of atactic and syndiotactic-rich ones bearing identical chiral, nonracemic pendant groups but the same sign Cotton effects in the absorption region of biphenyl side groups. This novel phenomenon was attributed to the cooperative effects of the tactic structure and the chiral pendant on the population of the helical sense of the polymer backbone: the chiral ortho -alkoxy terminal made the two phenyl rings of the pendant twist in an identical direction, regardless of the tactic structure, but distinguished the right- from left-handed main chain helices of syndiotactic- and isotactic-rich polymers. This study not only provided the first comprehensive insight into the connections between the main chain spatial configuration, helical conformation and the chiroptical properties but also a convenient way to obtain vinyl polymers with various chiral secondary structures from the same monomer.